2020
DOI: 10.1515/secm-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of multi-walled carbon nanotubes on the mechanical and damping properties of ultra-high performance concrete

Abstract: In this paper, the effects of multiwalled carbon nanotubes (MWCNTs) on the mechanical and damping properties of ultra-high performance concrete (UHPC) were investigated. The results show that the proper amount of MWCNTs can improve mechanical properties as well as the damping properties. For the mechanical properties, the compressive strength and flexural strength of the specimens increased with the increase of MWCNTs content in the range of 0~0.05% (mass ratio to cement). However, when the content of MWCNTs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This seemed to be related to CNT agglomeration, which created defect sites in the cementitious matrix and may even act as a crack initiator. Zhang et al [72] observed MWCNT agglomeration using SEM, which justified it as a major cause of the mechanical and damping properties of HPC with MWCNT incorporation.…”
Section: Mechanical Strengthmentioning
confidence: 97%
“…This seemed to be related to CNT agglomeration, which created defect sites in the cementitious matrix and may even act as a crack initiator. Zhang et al [72] observed MWCNT agglomeration using SEM, which justified it as a major cause of the mechanical and damping properties of HPC with MWCNT incorporation.…”
Section: Mechanical Strengthmentioning
confidence: 97%
“…The agglomeration of CNTs resulted in a significant number of CNTs failing to adhere to the polymer matrix, thereby creating regions with structural defects in the nanocomposite material. 52…”
Section: Thermal Analysismentioning
confidence: 99%
“…Therefore, NHCF has the best effect on improving the damping properties of cement mortar. However, OCF and NCF are attached to various hydration products and form strong bonds with the cement mortar matrix, preventing the fibers from debonding from the cement mortar matrix and hindering the dissipation of vibration energy (Zhang et al, 2020).…”
Section: Cement Mortar Matrix-fibers Shear Lag Modelmentioning
confidence: 99%